2022
DOI: 10.1186/s13046-022-02306-4
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol sensor SCAP contributes to sorafenib resistance by regulating autophagy in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most malignant tumors and the fourth leading cause of cancer-related death worldwide. Sorafenib is currently acknowledged as a standard therapy for advanced HCC. However, acquired resistance substantially limits the clinical efficacy of sorafenib. Therefore, further investigations of the associated risk factors are highly warranted. Methods We analysed a group of 78 HCC patients who received s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In this study, CSCs were linked to a survival advantage over non-CSCs after sorafenib treatment of tumor cells, resulting in a significant increase in the relative proportion of CSCs in all HCC cell lines tested, and this may be related to liver cancer recurrence after sorafenib treatment ( Xin et al, 2013 ). In addition, Mok et al (2022) showed that SREBP2-mediated cholesterol biosynthesis is crucial for the increase of hepatic CSCs, and deletion of sterol-regulatory element binding protein 2 (SREBP2) and its chaperone SCAP conferred sensitivity to tyrosine kinase inhibitors in tumor-bearing mice ( Li et al, 2022 ; Mok et al, 2022 ).…”
Section: Primary Drug Resistancementioning
confidence: 99%
“…In this study, CSCs were linked to a survival advantage over non-CSCs after sorafenib treatment of tumor cells, resulting in a significant increase in the relative proportion of CSCs in all HCC cell lines tested, and this may be related to liver cancer recurrence after sorafenib treatment ( Xin et al, 2013 ). In addition, Mok et al (2022) showed that SREBP2-mediated cholesterol biosynthesis is crucial for the increase of hepatic CSCs, and deletion of sterol-regulatory element binding protein 2 (SREBP2) and its chaperone SCAP conferred sensitivity to tyrosine kinase inhibitors in tumor-bearing mice ( Li et al, 2022 ; Mok et al, 2022 ).…”
Section: Primary Drug Resistancementioning
confidence: 99%
“…In cases where autophagy inhibition is harmful, the induction of autophagy is beneficial for TKI therapy. 352 Serine and arginine-rich splicing factor 1 (SRSF1) is an autophagy suppressor, and its knockdown may activate autophagy and inhibit the proliferation of gefitinib-resistant cancer cells. 353 Cannabidiol promotes mitochondrial autophagy in CML cells by activating transient receptor potential vanilloid type 2 (TRPV2).…”
Section: Mechanisms Of Tki Resistancementioning
confidence: 99%
“…In a recent study, SCAP was shown to be substantially expressed in HCC tissues and associated with sorafenib resistance. Lycorine, a specific SCAP inhibitor, triggered autophagy by elevating AMPK activity, increasing the HCC cells’ sensitivity to sorafenib [ 135 ].…”
Section: Natural Products Overcome Autophagy-mediated Tumor Drug Resi...mentioning
confidence: 99%